2007
DOI: 10.1002/lsm.20549
|View full text |Cite
|
Sign up to set email alerts
|

Low‐level light stimulates excisional wound healing in mice

Abstract: Background-Low levels of laser or non-coherent light, termed low-level light therapy (LLLT) have been reported to accelerate some phases of wound healing, but its clinical use remains controversial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
102
1
8

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 152 publications
(120 citation statements)
references
References 46 publications
(43 reference statements)
9
102
1
8
Order By: Relevance
“…Some of the animal studies investigating the effects of LLLT on wound healing have found similar results to the ones found in the in vitro studies, ranging from decreased inflammation and increased collagen and granulation tissue in the wound bed to increased tensile strength and faster epithelization [20][21][22][23].…”
Section: Lllt-mechanism Of Action On Cellular and Tissular Levelsupporting
confidence: 64%
“…Some of the animal studies investigating the effects of LLLT on wound healing have found similar results to the ones found in the in vitro studies, ranging from decreased inflammation and increased collagen and granulation tissue in the wound bed to increased tensile strength and faster epithelization [20][21][22][23].…”
Section: Lllt-mechanism Of Action On Cellular and Tissular Levelsupporting
confidence: 64%
“…LLLT has been shown to be beneficial in facilitating healing of slow or non-healing wounds in laboratory animals [11] and humans [12 -15] . LLLT stimulates cellular physiologic processes [16] .…”
Section: Introductionmentioning
confidence: 99%
“…10 Du ring the last 40 ye ars, its ef fi cacy in wo und re pa ir was in ves ti ga ted and sup por ted with many ani mal [13][14][15][16][17] and hu man stu di es. 20,21 Today, in many co un tri es ex cept Uni ted Sta tes, LLLT is wi dely used for the tre at ment of a va ri ety con diti ons inc lu ding ne u ro lo gic, den tal and der ma to logic di sor ders.…”
Section: Discussionmentioning
confidence: 99%
“…12 Alt ho ugh se ve ral stu di es ha ve in ves ti ga ted its the ra pe u tic bene fit on pres su re ul cers, the cli ni cal use of LLLT for wo und he a ling is still un der in ves ti ga ti on be ca u se many in ves ti ga tors re port conf lic ting fin dings in ani mal and hu man stu di es. [13][14][15][16][17][18][19][20][21] In the pre sent li te ra tu re, the com pa ra ti ve data of both tre at ment mo da li ti es con cer ning wo und he a ling is very li mi ted. 22 Mo re o ver, to the best of our know led ge, the re is no da ta that com pa re the two tre at ment mo da li ti es in ex ci si o nal wo und hea ling in terms of both his to pat ho lo gic and bi oc hemi cal chan ges.…”
mentioning
confidence: 99%